The vitamin D status of prison inmates. - Benjamin Udoka Nwosu; Louise Maranda; Rosalie Berry; Barbara Colocino; Carlos D Flores; Kerry Folkman; Thomas Groblewski; Patricia Ruze (PLoS ONE, 2014)
Introduction There is no comprehensive, systematic analysis of the vitamin D status of prisoners in the scientific literature. Objective To investigate the vitamin D status and its determinants in US prison inmates. Hypothesis Given the uniformity of dietary intake amongst inmates, vitamin D status will be determined by non-dietary factors such as skin pigmentation, security level-, and the duration of incarceration. Subjects and methods A retrospective study of 526 inmates (males, n=502, age 48.6 ± 12.5 years; females, n=24, age 44.1 ± 12.2) in Massachusetts prisons. Vitamin D sufficiency, insufficiency, and deficiency were respectively defined as a 25(OH)D concentration 75 nmol/L; 50 to 75 nmol/L; and <50 nmol/L. The Massachusetts Department of Correction Statement of Nutritional Adequacy stated that each inmate received the recommended daily allowance of vitamin D daily. Security level of incarceration was designated as minimum, medium, and maximum. Racial groups were categorized as Black, white, Asian, and Others. Results Serum 25(OH)D levels peaked in summer and autumn, and decreased in winter and spring. Vitamin D deficiency occurred in 50.5% of blacks, 29.3% of whites, and 14.3% of Asian inmates (p=0.007). Black inmates had significantly lower serum 25(OH)D level than white inmates at the maximum security level (p=0.015), medium security level (p=0.001), but not at the minimum security level (p=0.40). After adjusting for covariates black inmates at a maximum security level had a four-fold higher risk for vitamin D deficiency than white inmates at the same security level (OR 3.9 [95% CI 1.3-11.7]. Conclusions The vitamin D status of prison inmates is determined by skin pigmentation, seasons, and the security level of incarceration.